Humanization of Care from the Perspective of the Family Health Strategy Teams in a City in the Interior of São Paulo, Brazil (Revista Latino-Americana de Enfermagem, 2010)
This study analyzes the understanding of professionals composing teams of the Family Health Strategy concerning humanization of care. This qualitative survey was carried out in a city in the interior of São Paulo through interviews with 20 professionals. The data analysis method used was Interpretation of Meanings based on the hermeneutic-dialectic perspective. The meaning of humanization according to the interviewed professionals includes an enlarged view, respect for ethical principles and facilitated access. The difficulties refer to the lack of prepared professionals, excessive demand and deficiencies in service organization. The professionals propose to educate and qualify professionals, make activities adequate given the professionals' roles and improve the organization of services. The professionals demonstrate understanding of the meaning of humanization and acknowledge the need to cope with difficulties.